BORROWING GOODS LISTED APPLICATIONS USING VISUAL BASIC 6.0 - Aris Yudanto; Yuce Yuliani Skom., MM, Yuce Yuliani Skom., MM, (Jurnal Sistem Informasi, 2000)
With advances in both computer hardware and software, especially in Indonesia, it is expected that progress can be helpful in dealing with problems that are still done manually. Rental listing application process is performed in the computer stuff is very helpful, because the program listing of rental items include input data, edit data, display data, and security programs. The program listing applications made to the borrowing of goods can be used easily without the use of manuals. This application is made with the aid of Microsoft Visual Basic 6.0 software